Leadership Strategy in University Quality Control in the Digital Era Industry 4.0 - Rumagit, Selvie Serly; Rawis, Joulanda A.M.; Tambingon, Henny N.; Kambey, Joseph (JR Education, 2023)
The rapid growth of digital technology in the Industry 4.0 era has brought about significant changes in various aspects of society, including the education sector. As universities strive to improve the quality of education, effective leadership strategies are essential in implementing quality control measures. This article aims to examine leadership strategies in university quality control in the digital era of Industry 4.0. This study employs a qualitative approach using a case study method. The data was collected through interviews with university leaders and staff quality control, as well as through document analysis. The findings reveal that effective leadership strategies in university quality control in the digital era of Industry 4.0 involve the use of technology to monitor and evaluate educational processes, a collaboration between academic and administrative staff, and the implementation of a continuous improvement culture. Furthermore, this article highlights the challenges faced by university leaders in implementing effective measures of quality control in the digital era, including the need for continuous training of staff and the proper use of digital technology. This study provides valuable insights for university leaders and staff quality control in developing effective leadership strategies to ensure the delivery of quality education in the digital era of Industry 4.0.